Sha’ā’ir Qirā’ah Rawātib al-Ḥaddād fī Indūnīsīyā: Dirāsah Tamhīdīyah - Abdillah, Aam (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2003)
This article aims to provide a picture of the traditions of one of the ratib developed by the tariqah followers, namely ratlb al-Haddad, which is often linked to one of the authors and Sufi from Hadrami, Sayyid 'Abd Allah ibn 'Alwt al-Hnddad. In the Indonesian Muslim community, the tradition of rending ratib al-Haddad is believed to have its roots in the tenchings of 'Alawiyyah order. In several regions, such as Bekasi, West Jvan and in the Betawi community, for example, the reading of ratibib al-Haddad has become a tradition that is passed down from one generation to the next, and which is included on various occasions, such as major Islamic days of remembrance, and other religions celebrations.DOI: 10.15408/sdi.v10i3.626